A study on consumer perception towards buying China products among generation Y / Fatin Farahaini Mohamad Zamrie - Mohamad Zamrie, Fatin Farahaini (Faculty of Business and Management, 2015)
This research was conducted to carry out a study entitled “Consumer perception towards buying China product among Gen Y”. The purpose of this study is to investigate the key factors which influence the Gen Y consumer perception. The four independent variables are Country of Origin (COO), product type, product quality and price sensitivity. The sample size used for this study was 150. Data was obtained by using convenience sampling. The study seeks to identify the Gen Y consumer perception towards buying China product , to examine the relationship between independent variables (Country of Origin (COO), product type, product quality and price sensitivity) and dependent variable (Gen Y consumer perception) and to identify the most important variable on consumer perception towards buying China product among Gen Y. Finding shows that, there is a consumer perception towards buying China product and all independent variables (Country of Origin (COO), product type, product quality and price sensitivity) show significant relationship with the dependent variable (Gen Y consumer perception). The most significant variable on Gen Y consumer perception towards buying China product) is product type at at 0.105 (10.5%). Overall, researchers achieved to answer all objectives in the study.